Implementasi Etika Bisnis Islam pada BMT Usaha Artha Sejahtera (UAS) Bangilan Kabupaten Tuban - Ni’matul Jannah (Journal of Islamic Banking, 2021)
Business activities in the Islamic economy are based on the Qur'an and Al-Hadith, especially in Islamic financial institutions. BMT UAS Bangilan is a sharia cooperative with savings and loan service facilities. The operational system is in accordance with the Qur’an and Al-Hadith, so that the business runs in accordance with the proper Islamic economic system. In the view of Islam, there are many business transactions that contain Ghahar (uncertainty), playing, usury, which is detrimental to the Piha. BMT UAS Bangilan One of the Syari Cooperatives in Bangilan who implemented the Islamic Economic System. The Islamic economic system is applied so that in business activities always ethics is good and there will be no one who loses and is detrimental. The research method used is a qualitative method using observation, interviews and documentation techniques can be intensively reducing information to be more accurate. The data that has been obtained is then processed by interpreting into the sentence until it can be drawn conclusions as the results of the study. While the unturn of validity, the author uses the source triangulation. After research, it can be drawn by BMT conclusions BRS has implemented Islamic business ethics in accordance with the Qur'an and Al-Hadith. Normally applies can be seen from no activity that harms one of the parties (members and BMT UAS Bangilan). Transparent norms can be seen from the openness between members and BMT UAS Bangilan. Professional norms can be seen from the staff of employee employees working well. The norm of unity can be seen from vertical relationships to God. Balance norms can be seen from the existence of horizontal relationships with humans (relationship between managers, employees and BMT UAS’s members) with the purpose of world welfare and the hereafter. Free woe norms can be seen from several indicators that show BMT UAS of the freedom of members in the transaction, because absolute freedom only belongs to God. The norm of responsibility can be seen from the responsibility of BMT UAS to members.